2020
DOI: 10.1152/ajpcell.00253.2020
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Fbxl22, a novel skeletal muscle atrophy-promoting E3 ubiquitin ligase

Abstract: Muscle-specific E3 ubiquitin ligases have been identified in muscle atrophy-inducing conditions. The purpose of the current study was to explore the functional role of Fbxl22, and a newly identified splice variant (Fbxl22-193), in skeletal muscle homeostasis and neurogenic muscle atrophy. In mouse C2C12 muscle cells, promoter fragments of the Fbxl22 gene were cloned and fused with the secreted alkaline phosphatase reporter gene to assess the transcriptional regulation of Fbxl22. The tibialis anterior muscles o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…However, recently we showed that transfection of unchallenged TA muscle with Fbxl22, an F-box E3 ligase, resulted in muscle fiber degeneration demonstrating that certain F-box proteins can induce a phenotype when transfected into muscle. 22 Clearly, MAFbx plays an important role in skeletal muscle atrophy, which is distinct from MuRF1. Additional studies are needed to identify the in vivo substrates of MAFbx and to find how ubiquitination of those substrates alters the function and/or structure of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently we showed that transfection of unchallenged TA muscle with Fbxl22, an F-box E3 ligase, resulted in muscle fiber degeneration demonstrating that certain F-box proteins can induce a phenotype when transfected into muscle. 22 Clearly, MAFbx plays an important role in skeletal muscle atrophy, which is distinct from MuRF1. Additional studies are needed to identify the in vivo substrates of MAFbx and to find how ubiquitination of those substrates alters the function and/or structure of skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the temporal and spatial regulation of murine Fbxl22 was elucidated by Hughes and co-workers for skeletal muscles [126]. Intriguingly, the authors uncovered a novel Fbxl22 splice isoform in muscles.…”
Section: Fbxl22mentioning
confidence: 99%
“… 35 It would be interesting to further investigate the proteasome‐mediated degradation pathway through other relevant ubiquitin ligases, as it seems likely that many others, with different substrate‐specificity, are involved in cancer cachexia. Fbxl22 36 and Musa1, 37 for example, would be valuable targets as they have been recently identified in the context of muscle atrophy. Analysis of myostatin‐related and IGF‐related signalling pathways would also be interesting to further improve our understanding on the interplay of molecular mechanisms underlying skeletal muscle wasting during cancer cachexia (refer to review 38 ).…”
Section: Discussionmentioning
confidence: 99%